The Experience of Women Receiving Mastectomy Care in an Acute Surgical Ward: A Qualitative Study - Celine Frost; Raewyn Lesā; Sandra Richardson (Wiley, 2024)
ABSTRACT Aim The research aim was to understand the inpatient experience of women who received postoperative care for mastectomy surgery in an acute surgical ward. Design A Qualitative Descriptive Research design was used. Methods The lead researcher conducted individual semi‐structured interviews with 10 women who received postoperative care following mastectomy surgery in an acute hospital surgical ward. The transcribed interview data was analysed using a thematic analysis. Results A mastectomy is a momentous event in any woman's life. In the initial post‐operative phase, the physical intrusion of surgery, aesthetics of the ward, and mixed‐gender rooms were all found to influence the women's journey towards holistic recovery. Therapeutic care from all in the healthcare team and a ward setting conducive to recovery were identified as favourable influences towards physical and emotional healing. Conclusion Recognising that a mastectomy 'is not just physical' may help the breast care team optimise the first 24 h of postoperative care in preparation for the challenges the women may face on discharge. Implications for the Profession and/or Patient Care In an acute inpatient setting, a women's physical needs may be prioritised over the psychological and emotional ramifications of a mastectomy. Post‐operative inpatient care for breast cancer surgery requires not only professional competency with clinical and technical tasks, but therapeutic nursing and communication skills to support women's psychological needs. Patient or Public Contribution The findings were drawn from 10 women, narrating their inpatient experience for breast cancer surgery. All women had undergone a unilateral or bilateral mastectomy following breast cancer.